An Assessment of Juvenile Justice Reform in Ohio: Impact on Youth Placement and Recidivism From 2008 to 2015 - Park, Insun (Crime & delinquency, 2024)
Juvenile justice systems across the U.S. have undergone transformations over the last 20?years. These efforts include deliberate attempts and policy decisions enacted to reduce the number of incarcerated youths. Ohio has implemented a series of initiatives in its juvenile justice system designed to reduce reliance on state custody of youth in favor of local alternatives. Using Ohio?s juvenile justice systems as a focal case, this study assessed reform initiatives on the reduction in youth incarceration and recidivism. Our analyses of 5,000 youths sampled from cases processed between 2008 and 2015 revealed a sustained trend in diverting youth from incarceration, most conspicuously among low risk youths. The diverted population, after adjusting for covariates through propensity score techniques, had lower rates of incarceration compared to the youths in state residential facilities. The outcome of the reform initiatives is discussed in terms of supporting redirection and reinvestment of finite resources and refining intervention strategies in implementing change in juvenile justice.